Trunk rotation torques through the hip joints during the one- and two-handed backhand tennis strokes - Akutagawa, S.; Kojima, T. (Journal of Sports Sciences, 2005)
The aim of the present study was to compare kinetically the roles of the lower extremities in generating trunk rotation in the tennis one-handed and two-handed backhand strokes. Fourteen male collegiate tennis players, seven with a preference for the one- and seven with a preference for the two-handed technique, were recruited as participants. The motion of each backhand stroke was filmed using two high-speed cine-cameras, and the ground reaction forces on the feet were measured separately using two force platforms to determine the joint moments and joint reaction forces at the hip, knee and ankle joints. A significant difference in hip joint moments between the two types of stroke was found in the phase from the start of forward rotation of the pelvis to the start of racket forward movement. For trunk rotation, the one-handed backhand players exerted a large joint moment in the front leg, whereas the two-handed backhand players exerted a large joint moment in the back leg. The exertion of a large hip joint moment in the latter stroke was comparable with the exertion in a forehand stroke reported previously.